Nano oil displacement agent for fracturing as well as preparation method and application of nano oil displacement agent

By using MoS2 nanosheets and surfactants prepared under high mineralization and high temperature conditions, the problem of poor stability of traditional oil repellent is solved, and good permeability and reservoir transformation is achieved. ability.

CN119391394AActive Publication Date: 2025-02-07CHINA NAT OFFSHORE OIL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411477095.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-07
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

Traditional oil-repellents have poor stability under high mineralization and high temperatures, and cannot be used for integrated oil-repellent fracturing fluid under complex formation conditions.

Method used

A nano-oil repellent prepared by combining MoS2 nanosheets and surfactant in deionized water was prepared by magnetic stirring, ultrasonic oscillation and centrifugal washing. The temperature and salt-resistant functional nano-oil repellent was prepared.

Benefits of technology

The nano-oil repellent exhibits good stability and oil repellency under high mineralization and high temperature conditions, which improves the reservoir transformation capability and solves the problem of weakening the effect of traditional oil repellent under complex working conditions. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391394A_ABST
    Figure CN119391394A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of oil and gas reservoir transformation and yield increase, and provides a nanometer oil displacement agent for fracturing and a preparation method and application thereof.The method comprises the steps that thiourea, molybdenum trioxide and thioacetamide are added into deionized water according to the proportion to be mixed, and stirring is conducted till sufficient mixing is conducted to form a mixed solution; adding the mixed solution into a reaction kettle with a polytetrafluoroethylene lining for reaction, and taking out a synthesized crude MoS2 mixed solution after the reaction; the crude MoS2 is subjected to ultrasonic oscillation washing with an ethanol solution and deionized water, and a pure MoS2 mixed solution is obtained; the preparation method comprises the following steps: preparing MoS2 nanosheets from a pure MoS2 mixed solution, weighing the MoS2 nanosheets and a surfactant, adding the MoS2 nanosheets and the surfactant into deionized water, and fully stirring; and centrifugally washing the product with deionized water, and re-dispersing the product in deionized water to obtain the temperature-resistant and salt-resistant functional nano oil displacement agent. According to the method, the imbibition oil displacement effect under the high-salinity and high-temperature stratum working conditions can be improved, and the reservoir transformation capacity is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and gas reservoir transformation and production increase, and in particular to a nano oil displacement agent for fracturing, a preparation method and application thereof. Background Art

[0002] As unconventional oil and gas exploration and development move from land to deep sea, offshore shale oil has become the main force for resource replacement and stable production and increase. Offshore fracturing development and construction are very marine, and high-mineralization formation water and seawater place high demands on the stability of fracturing fluids. After traditional oil displacement agents are injected into the formation, they interact with the formation reservoir and reservoir fluids to reduce the oil-water interfacial tension and increase the recovery rate.

[0003] However, the above-mentioned traditional oil-displacing agents have poor stability under high salinity and high temperature, and cannot be used in integrated imbibition and oil-displacing fracturing fluids under complex formation conditions. Summary of the invention

[0004] The purpose of the present invention is to solve at least one technical problem in the background technology and to provide a nano oil displacement agent for fracturing and a preparation method and application thereof.

[0005] To achieve the above object, the present invention provides a nano oil-displacing agent for fracturing, wherein the nano oil-displacing agent for fracturing is prepared by adding MoS2 nanosheets and a surfactant to deionized water and washing with deionized water. The molecular structure of the MoS2 nanosheets is:

[0006]

[0007] In the formula, R1 is a hydrophilic group selected from one or more of the following structures:

[0008]

[0009]

[0010] R2 is a lipophilic group with the structure:

[0011]

[0012] Among them, n=6-16.

[0013] According to one aspect of the present invention, the raw materials for preparing the MoS2 nanosheets include at least two of ammonium molybdate tetrahydrate, molybdenum trioxide, thiourea, urea, and thioacetamide.

[0014] According to one aspect of the present invention, the surfactant includes anionic surfactants, cationic surfactants, zwitterionic surfactants and nonionic surfactants;

[0015] The anionic surfactant is at least one of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate;

[0016] The cationic surfactant is at least one of dodecyldimethylbenzylammonium chloride and hexadecyltrimethylammonium bromide;

[0017] The zwitterionic surfactant is at least one of lauryl amide propyl betaine and nonylphenol betaine;

[0018] The nonionic surfactant is at least one of lauryl alcohol polyoxyethylene ether and nonylphenol polyoxyethylene ether ammonium sulfate.

[0019] To achieve the above object, the present invention also provides a method for preparing a nano oil-displacing agent for fracturing, comprising:

[0020] Thiourea, molybdenum trioxide, and thioacetamide were added to 100 ml of deionized water in a ratio of 1:1:10, and stirred with a magnetic stirrer at a speed of 200 r / min for 2 h until the mixture was fully mixed to form a mixed solution;

[0021] The mixed solution is added into a reactor with a polytetrafluoroethylene liner for reaction. After the reaction is completed and cooled, the reactor is cooled with water, and the synthesized crude MoS2 mixed solution is taken out;

[0022] Pour the crude MoS2 mixed solution into a centrifuge tube, and use ethanol solution and deionized water to ultrasonically shake the liquids to mix them thoroughly, and then centrifuge them to remove the upper liquid to obtain a pure MoS2 mixed solution.

[0023] The pure MoS2 mixed liquid is freeze-dried to form MoS2 nanosheets, and the MoS2 nanosheets and surfactant are weighed and added to deionized water, and ultrasonic treatment is performed to mix them evenly to form a MoS2 mixed liquid, and then the obtained MoS2 mixed liquid is fully stirred; the product is washed by centrifugation with deionized water for multiple times, and then redispersed in the dispersion to obtain a temperature-resistant and salt-resistant functional nano oil-displacing agent.

[0024] According to one aspect of the present invention, the rotation speed of the reactor is 800 r / min, the reaction temperature is 220° C., and the reaction time is 12 h.

[0025] According to one aspect of the present invention, the rotation speed of the centrifuge is 8000-10000 r / min.

[0026] According to one aspect of the present invention, the crude MoS2 mixed solution is poured into a centrifuge tube and ultrasonically shaken three times with an ethanol solution and deionized water respectively.

[0027] According to one aspect of the present invention, the dispersion liquid is isopropyl alcohol or deionized water.

[0028] According to one aspect of the present invention, the concentration of the dispersion is 0.01 wt %.

[0029] According to one aspect of the present invention, the surfactant concentration is 0.1-0.3 wt %.

[0030] According to one aspect of the present invention, the surfactant is at least one of dodecanethiol, sodium dodecylbenzene sulfonate, nonylphenol polyoxyethylene ether ammonium sulfate, and nonylphenol betaine.

[0031] To achieve the above object, the present invention also provides a use of the above nano oil-displacing agent for fracturing in oil and gas reservoir reconstruction and production increase.

[0032] According to the scheme of the present invention, the heat-resistant and salt-resistant functionalized nano oil-displacing agent of the present invention is a nano oil-displacing agent produced by a new synthesis method. The oil-displacing agent has good salt resistance and temperature resistance, can improve the imbibition oil-displacing effect under high mineralization and high temperature formation working conditions, and enhance the reservoir transformation capacity.

[0033] The particle size of the MoS2 nanosheets synthesized by the present invention is 10-20nm, which is significantly smaller than the particle size of conventional MoS2 nanoflowers, and the dispersion performance is more stable.

[0034] The preparation method of the nano oil-displacing agent of the present invention is simple, easy to operate, and easy to control. The product type (powder or liquid) can be customized according to on-site requirements.

[0035] The nano oil-displacing agent of the present invention can be used for fracturing construction, reservoir transformation, and imbibition oil displacement under high salinity and seawater working conditions, and can solve the problem of unconventional oil and gas fracturing and extraction integration, and prevent the problem of weakened effect of the oil-displacing agent under complex working conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Schematically showing a scanning electron microscope image of molybdenum disulfide nanosheets synthesized using thiourea, molybdenum trioxide, and thioacetamide in Example 1;

[0037] Figure 2 Schematically showing a scanning electron microscope image of molybdenum disulfide nanosheets synthesized using thiourea and ammonium molybdate tetrahydrate in Example 3. Specific embodiments

[0038] The content of the present invention will now be discussed with reference to exemplary embodiments. It should be understood that the embodiments discussed are only to enable those skilled in the art to better understand and thus implement the content of the present invention, rather than implying any limitation on the scope of the present invention.

[0039] As used herein, the term “including” and variations thereof are to be interpreted as open-ended terms meaning “including, but not limited to.” The term “based on” is to be interpreted as “based, at least in part, on.” The terms “one embodiment” and “an embodiment” are to be interpreted as “at least one embodiment.”

[0040] Example 1

[0041] 1) Add thiourea, molybdenum trioxide and thioacetamide in a ratio of 1:1:10 to 100 ml of deionized water, and stir with a magnetic stirrer at a speed of 200 r / min for 2 h until fully mixed to form a mixed solution;

[0042] 2) adding the mixed solution to a high-temperature and high-pressure reactor with a polytetrafluoroethylene liner, reacting at a speed of 800 r / min and a temperature of 220° C. for 12 h, cooling the reactor with water after cooling, and taking out the synthesized MoS2 mixed solution (crude MoS2 mixed solution);

[0043] 3) Pour the prepared MoS2 mixed solution into a centrifuge tube, and wash it with ethanol solution and deionized water by ultrasonic vibration respectively to make the liquids fully mixed, and centrifuge it at a certain speed to skim off the upper liquid, and wash it repeatedly for 6 times until the upper liquid is clear to obtain a clean MoS2 mixed solution (pure MoS2 mixed solution);

[0044] 4) freeze-drying the washed MoS2 mixed solution to form MoS2 nanosheets, such as Figure 1 As shown, MoS2 nanosheets and a surfactant of a 1,3-dialkyl glycerol ether derivative are weighed and added to deionized water, and ultrasonic treatment is performed to mix them evenly to form a MoS2 mixed solution, and then the obtained MoS2 mixed solution is fully stirred; the product is washed by centrifugation with deionized water for multiple times, and then redispersed in deionized water to finally obtain a temperature-resistant and salt-resistant functionalized nano oil-displacing agent.

[0045] Example 2

[0046] 1) Add thiourea, molybdenum trioxide and thioacetamide in a ratio of 1:1:15 to 100 ml of deionized water, and stir with a magnetic stirrer at a speed of 200 r / min for 2 h until fully mixed to form a mixed solution;

[0047] 2) adding the mixed solution to a high-temperature and high-pressure reactor with a polytetrafluoroethylene liner, reacting at a speed of 800 r / min and a temperature of 220° C. for 12 h, cooling the reactor with water after cooling, and taking out the synthesized MoS2 mixed solution;

[0048] 3) Pour the prepared MoS2 mixed solution into a centrifuge tube, and wash it with ethanol solution and deionized water by ultrasonic vibration respectively to make the liquids fully mixed, and centrifuge it at a certain speed to skim off the upper liquid, and wash it repeatedly for 6 times until the upper liquid is clear to obtain a clean MoS2 mixed solution;

[0049] 4) freeze-drying the washed MoS2 mixed solution to form MoS2 nanosheets, weighing MoS2 nanosheets and nonylphenol polyoxyethylene ether ammonium sulfate, adding them to deionized water, ultrasonically treating and mixing them evenly to form a MoS2 mixed solution, and then stirring the obtained MoS2 mixed solution sufficiently; after the product was centrifuged and washed with deionized water for multiple times, it was redispersed in deionized water to finally obtain a heat-resistant and salt-resistant functionalized nano oil-displacing agent.

[0050] Example 3

[0051] 1) Add thiourea and ammonium molybdate tetrahydrate into 100 ml of deionized water in a ratio of 2:1, and stir with a magnetic stirrer at a speed of 200 r / min for 2 h until fully mixed to form a mixed solution;

[0052] 2) adding the mixed solution to a high-temperature and high-pressure reactor with a polytetrafluoroethylene liner, reacting at a speed of 800 r / min and a temperature of 220° C. for 12 h, cooling the reactor with water after cooling, and taking out the synthesized MoS2 mixed solution;

[0053] 3) Pour the prepared MoS2 mixed solution into a centrifuge tube, and wash it with ethanol solution and deionized water by ultrasonic vibration respectively to make the liquids fully mixed, and centrifuge it at a certain speed to skim off the upper liquid, and wash it repeatedly for 6 times until the upper liquid is clear to obtain a clean MoS2 mixed solution;

[0054] 4) freeze-drying the washed MoS2 mixed solution to form MoS2 nanosheets, such as Figure 2 As shown, MoS2 nanosheets and a surfactant of a 1,3-dialkyl glycerol ether derivative are weighed into deionized water, and ultrasonic treatment is performed to mix them evenly to form a MoS2 mixed solution, and then the obtained MoS2 mixed solution is fully stirred; the product is washed by centrifugation with deionized water for multiple times, and then redispersed in deionized water to finally obtain a temperature-resistant and salt-resistant functionalized nano oil-displacing agent.

[0055] Example 4

[0056] 1) Add thiourea, molybdenum trioxide and thioacetamide in a ratio of 1:1:10 to 100 ml of deionized water, and stir with a magnetic stirrer at a speed of 200 r / min for 2 h until fully mixed to form a mixed solution;

[0057] 2) adding the mixed solution to a high-temperature and high-pressure reactor with a polytetrafluoroethylene liner, reacting at a speed of 800 r / min and a temperature of 220° C. for 12 h, cooling the reactor with water after cooling, and taking out the synthesized MoS2 mixed solution;

[0058] 3) Pour the prepared MoS2 mixed solution into a centrifuge tube, and wash it with ethanol solution and deionized water by ultrasonic vibration respectively to make the liquids fully mixed, and centrifuge it at a certain speed to skim off the upper liquid, and wash it repeatedly for 6 times until the upper liquid is clear to obtain a clean MoS2 mixed solution;

[0059] 4) freeze-drying the washed MoS2 mixed solution to form MoS2 nanosheets, weighing MoS2 nanosheets (0.01wt%) and a surfactant of a 1,3-dialkyl glycerol ether derivative (0.1wt%), adding them to deionized water, ultrasonically treating and mixing them to form a MoS2 mixed solution, and then stirring the obtained MoS2 mixed solution sufficiently; after washing the product by centrifugation with deionized water for multiple times, redispersing it in deionized water, and finally obtaining a temperature-resistant and salt-resistant functionalized nano oil-displacing agent.

[0060] Example 5

[0061] 1) Add thiourea, molybdenum trioxide and thioacetamide in a ratio of 1:1:10 to 100 ml of deionized water, and stir with a magnetic stirrer at a speed of 200 r / min for 2 h until fully mixed to form a mixed solution;

[0062] 2) adding the mixed solution to a high-temperature and high-pressure reactor with a polytetrafluoroethylene liner, reacting at a speed of 800 r / min and a temperature of 220° C. for 12 h, cooling the reactor with water after cooling, and taking out the synthesized MoS2 mixed solution;

[0063] 3) Pour the prepared MoS2 mixed solution into a centrifuge tube, and wash it with ethanol solution and deionized water by ultrasonic vibration respectively to make the liquids fully mixed, and centrifuge it at a certain speed to skim off the upper liquid, and wash it repeatedly for 6 times until the upper liquid is clear to obtain a clean MoS2 mixed solution;

[0064] 4) freeze-drying the washed MoS2 mixed solution to form MoS2 nanosheets, weighing MoS2 nanosheets (0.01wt%) and a surfactant of a 1,3-dialkyl glycerol ether derivative (0.2wt%), adding them to deionized water, ultrasonically treating and mixing them to form a MoS2 mixed solution, and then stirring the obtained MoS2 mixed solution sufficiently; after washing the product by centrifugation with deionized water for multiple times, redispersing it in deionized water, and finally obtaining a temperature-resistant and salt-resistant functionalized nano oil-displacing agent.

[0065] Example 6

[0066] 1) Add thiourea, molybdenum trioxide and thioacetamide in a ratio of 1:1:10 to 100 ml of deionized water, and stir with a magnetic stirrer at a speed of 200 r / min for 2 h until fully mixed to form a mixed solution;

[0067] 2) adding the mixed solution to a high-temperature and high-pressure reactor with a polytetrafluoroethylene liner, reacting at a speed of 800 r / min and a temperature of 220° C. for 12 h, cooling the reactor with water after cooling, and taking out the synthesized MoS2 mixed solution;

[0068] 3) Pour the prepared MoS2 mixed solution into a centrifuge tube, and wash it with ethanol solution and deionized water by ultrasonic vibration respectively to make the liquids fully mixed, and centrifuge it at a certain speed to skim off the upper liquid, and wash it repeatedly for 6 times until the upper liquid is clear to obtain a clean MoS2 mixed solution;

[0069] 4) freeze-drying the washed MoS2 mixed solution to form MoS2 nanosheets, weighing MoS2 nanosheets (0.01wt%) and a surfactant of a 1,3-dialkyl glycerol ether derivative (0.3wt%), adding them to deionized water, ultrasonically treating and mixing them to form a MoS2 mixed solution, and then stirring the obtained MoS2 mixed solution sufficiently; after washing the product by centrifugation with deionized water for multiple times, redispersing it in deionized water, and finally obtaining a temperature-resistant and salt-resistant functionalized nano oil-displacing agent.

[0070] Test Example 1

[0071] 1) The temperature-resistant and salt-resistant functionalized nanosheets obtained in Examples 1 to 6 were subjected to a particle size test;

[0072] 2) The test method is: use deionized water to prepare the functionalized nanosheet dispersion with a concentration of 0.01wt%, use an ultrasonic multifunctional testing machine for ultrasonic dispersion, and use a Delsa Nano particle size analyzer to perform particle size testing. The test results are shown in Table 1:

[0073] 3) Table 1

[0074]

[0075]

[0076] 4) Analysis of results: It can be seen from Table 1 that the particle size of the functionalized nanosheets synthesized is all in the range of 15-70 nm. The particle size of the nanosheets obtained in Example 3 is relatively large, and the particle size of the nanosheets obtained in Examples 1, 2, 4, 5, and 6 is relatively small, smaller than the pore size of the core, and can enter the tiny pores of the core, interact with the crude oil, and drive out a large amount of remaining oil in the reservoir, thereby improving the crude oil recovery rate.

[0077] Test Example 2

[0078] 1) The heat-resistant and salt-resistant functionalized nano oil-displacing agents obtained in Examples 1 to 6 were subjected to an interfacial tension test;

[0079] 2) The test method is: use seawater to prepare the functionalized nano oil-displacing agent, the concentration is 0.2wt%, use an ultrasonic multifunctional testing machine for ultrasonic dispersion, use a TX500C rotating droplet interfacial tension meter to test the interfacial tension, turn on the circulating water bath system, set the test temperature in the experiment to the corresponding temperature in the formation, adjust the speed to 6000r / min, the oil sample is crude oil, start the instrument to test the interfacial tension, and the test results are shown in Table 2:

[0080] 3) Table 2

[0081]

[0082]

[0083] 4) Result analysis: From Table 2, it can be seen that the functionalized nano oil-displacing agent has good salt tolerance. When the seawater mineralization increases from 20000 mg / L to 30000 mg / L, the functionalized nanosheets do not precipitate, have good stability, and have excellent salt tolerance. The synthesized functionalized nanosheet oil-displacing agent has good interfacial activity. The interfacial tension of Examples 1, 2, and 3 can reach 10 -3 mN / m. In Examples 4, 5 and 6, the nano oil-displacing agents modified with surfactants of 1,3-dialkyl glycerol ether derivatives can reduce the interfacial tension to an ultra-low level as the proportion of the surfactant increases, and have good universality.

[0084] Test Example 3

[0085] 1) The heat-resistant and salt-resistant functionalized nano oil-displacing agents obtained in Examples 1 to 6 were subjected to an imbibition oil displacement test;

[0086] 2) The test method is: measure the physical properties of a sandstone core column from a certain place, dry it in an electric constant temperature drying oven at 80°C for 7 days, and then vacuum saturate it with oil. The saturated oil temperature is 120°C and the saturated oil pressure is 20Mpa. After saturation, weigh it and calculate the saturated oil mass. The saturated oil core is placed in an absorption bottle filled with a heat-resistant and salt-resistant functionalized nano oil-displacing agent configured with seawater. The water bath temperature is 80°C. In order to facilitate reading and reduce errors, the oil-displacing agent is filled to the 0.2ml scale of the absorption bottle. Continue to absorb and displace oil for 7 days until no oil is produced. The oil displacement efficiency is calculated. The test results are shown in Table 3:

[0087] 3) Table 3

[0088]

[0089]

[0090] 4) Analysis of results: It can be seen from Table 3 that the oil displacement efficiency of the synthetically configured functionalized nano oil-displacing agent is significantly improved compared with the imbibition oil displacement efficiency under formation water conditions. The particle size of the nanosheets synthesized in Examples 1-6 is 10-70nm, and the interfacial tension of Examples 4-6 can reach ultra-low. The nano oil-displacing agent can penetrate into the tiny pores of the sandstone core, greatly improving the crude oil utilization rate, and the oil displacement efficiency can reach 40%-60%. As the surface tension drops to ultra-low, the oil displacement efficiency is further improved. It can be seen that the interfacial activity is good and the crude oil is easy to deform, which proves that it has good stability under high mineralization and high temperature.

[0091] The above experimental results show that the functionalized nano oil-displacing agent synthesized by introducing heat-resistant and salt-resistant functional groups has good heat and salt resistance, can meet the requirements of imbibition oil displacement performance under high mineralization, seawater and high temperature, and has broad application prospects.

[0092] According to the above scheme of the present invention, the heat-resistant and salt-resistant functionalized nano oil-displacing agent of the present invention is a nano oil-displacing agent prepared by a new synthesis method. The oil-displacing agent has good salt resistance and temperature resistance, can improve the imbibition oil-displacing effect under high mineralization and high temperature formation working conditions, and enhance the reservoir transformation capacity.

[0093] The particle size of the MoS2 nanosheets synthesized by the present invention is 10-20nm, which is significantly smaller than the particle size of conventional MoS2 nanoflowers, and the dispersion performance is more stable.

[0094] The preparation method of the nano oil-displacing agent of the present invention is simple, easy to operate, and easy to control. The product type (powder or liquid) can be customized according to on-site requirements.

[0095] The nano oil-displacing agent of the present invention can be used for fracturing construction, reservoir transformation, and imbibition oil displacement under high salinity and seawater working conditions, and can solve the problem of unconventional oil and gas fracturing and extraction integration, and prevent the problem of weakened effect of the oil-displacing agent under complex working conditions.

[0096] Finally, it should be noted that the above embodiments are only preferred embodiments, which are only used to illustrate the technical solutions of the present invention rather than to limit them. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A nano oil displacement agent for fracturing, characterized in that: The nano oil displacement agent for fracturing is obtained by adding MoS2 nanosheets and surfactants into deionized water and washing with deionized water. The molecular structure of the MoS2 nanosheets is: In the formula, R1 is a hydrophilic group selected from one or more of the following structures: R2 is a lipophilic group with the structure: Among them, n=6-16.

2. The nano oil-displacing agent for fracturing according to claim 1, characterized in that: The raw materials for preparing the MoS2 nanosheets include at least two of ammonium molybdate tetrahydrate, molybdenum trioxide, thiourea, urea, and thioacetamide.

3. The nano oil-displacing agent for fracturing according to claim 1, characterized in that: The surfactant includes anionic surfactant, cationic surfactant, zwitterionic surfactant and nonionic surfactant; The anionic surfactant is at least one of sodium dodecylbenzene sulfonate and sodium dodecyl sulfate; The cationic surfactant is at least one of dodecyldimethylbenzylammonium chloride and hexadecyltrimethylammonium bromide; The zwitterionic surfactant is at least one of lauryl amide propyl betaine and nonylphenol betaine; The nonionic surfactant is at least one of lauryl alcohol polyoxyethylene ether and nonylphenol polyoxyethylene ether ammonium sulfate.

4. A method for preparing a nano oil-displacing agent for fracturing, characterized in that: include: Thiourea, molybdenum trioxide, and thioacetamide were added to 100 ml of deionized water in a ratio of 1:1:10, and stirred with a magnetic stirrer at a speed of 200 r / min for 2 h until the mixture was fully mixed to form a mixed solution; The mixed solution is added into a reactor with a polytetrafluoroethylene liner for reaction. After the reaction is completed and cooled, the reactor is cooled with water, and the synthesized crude MoS2 mixed solution is taken out; Pour the crude MoS2 mixed solution into a centrifuge tube, and use ethanol solution and deionized water to ultrasonically shake the liquids to mix them thoroughly, and then centrifuge them to remove the upper liquid to obtain a pure MoS2 mixed solution. The pure MoS2 mixed liquid is freeze-dried to form MoS2 nanosheets, and the MoS2 nanosheets and surfactant are weighed and added to deionized water, and ultrasonic treatment is performed to mix them evenly to form a MoS2 mixed liquid, and then the obtained MoS2 mixed liquid is fully stirred; the product is washed by centrifugation with deionized water for multiple times, and then redispersed in the dispersion to obtain a temperature-resistant and salt-resistant functional nano oil-displacing agent.

5. The method for preparing a nano oil-displacing agent for fracturing according to claim 4, characterized in that: The rotation speed of the reactor is 800 r / min, the reaction temperature is 220° C., and the reaction time is 12 h.

6. The method for preparing a nano oil-displacing agent for fracturing according to claim 4, characterized in that: The rotation speed of the centrifuge is 8000-10000r / min.

7. The method for preparing a nano oil-displacing agent for fracturing according to claim 4, characterized in that: The crude MoS2 mixed solution was poured into a centrifuge tube and ultrasonically shaken three times with ethanol solution and deionized water respectively.

8. The method for preparing a nano oil-displacing agent for fracturing according to claim 4, characterized in that: The dispersion liquid is isopropanol or deionized water.

9. The method for preparing a nano oil-displacing agent for fracturing according to claim 4, characterized in that: The concentration of the MoS2 dispersion is 0.01-0.3 wt%.

10. The method for preparing a nano oil-displacing agent for fracturing according to claim 4, characterized in that: The surfactant concentration is 0.1-0.3 wt %.

11. The method for preparing a nano oil-displacing agent for fracturing according to claim 4, characterized in that: The surfactant is at least one of dodecanethiol, sodium dodecylbenzene sulfonate, nonylphenol polyoxyethylene ether ammonium sulfate, and nonylphenol betaine.

12. Use of the nano oil-displacing agent for fracturing according to any one of claims 1 to 3 in oil and gas reservoir reconstruction and production increase.

Citation Information

Patent Citations

  • Method for preparing MoS2 microspheres by solvent hot method

    CN101851006A

  • Modified MoS2 nano material and preparation method thereof

    CN109943310A

  • Method for preparing fracturing fluid from MoS2 nanosheet

    CN110452678A

  • Method for preparing multifunctional slick water based on MOS2 nano sheet

    CN110511734A

  • Preparation method and application of 2D nanosheet oil displacement agent

    CN111454707A